Kinetic theory of dusty plasmas and effective grain interactions - Zagorodny, A.G.; Filippov, A.V.; Pal', A.F.; Starostin, A.N.; Momot, A.I. (Вопросы атомной науки и техники, 2008)
The basic points of the consistent kinetic theory of dusty plasmas is discussed. The equations for microscopic phase densities of plasma particles and grains are formulated. Using such equations it is possible to derive the kinetic equations, taking into account both elastic and inelastic particle collisions. Obtained equations are used for kinetic description of effective grain-grain potentials. Обговорюються основні положення послідовної кінетичної теорії запорошеної плазми. Наведено рівняння для мікроскопічних фазових густин для плазмових частинок і порошинок. Показано, що, використовуючи такі рівняння, можна сформулювати кінетичні рівняння для запорошеної плазми з урахуванням пружних і непружних зіткнень частинок та поглинання електронів та іонів порошинками. Розглянуто кінетичний опис ефективних потенціалів взаємодії порошинок у плазмі. Обсуждаются основные положения последовательной кинетической теории пылевой плазмы. Приведены уравнения для микроскопических фазовых плотностей для плазменных частиц и пылинок. Показано, что, используя такие уравнения, можно сформулировать кинетические уравнения для пылевой плазмы, учитывающие упругие и неупругие столкновения частиц и поглощение электронов и ионов пылинками. Выполнены кинетические расчеты эффективных потенциалов взаимодействия пылинок в плазме.